Contact-free thermal expansion measurement of very soft elastomers using digital image correlation. (May 2016) - Lee, Tae-Ik; Kim, Min Sung; Kim, Taek-Soo
Abstract: The coefficient of thermal expansion (CTE) is a critical material property that represents the dimensional stability of a material under thermal loading. For soft materials such as elastomers, accurate measurement of the CTE is challenging due to the severe local deformation of the specimen in contact with the measuring apparatus. In this paper, a contact-free CTE measurement method is introduced for soft polymers using three-dimensional digital image correlation. The accuracy of the method was validated using various reference materials. The CTEs of extremely soft silicone elastomers were successfully measured with high precision, where the specimens were suspended in order to ensure free expansion of the compliant and adherent materials. Moreover, the high-throughput capability of the method was demonstrated through simultaneously evaluating multiple specimens. For polydimethylsiloxane (PDMS), the effects of the mixing ratio and curing temperature on the CTE and fractional free volume (FFV) of the polymer network were investigated, where the correlation between the CTE and FFV was quantitatively verified. The proposed method is expected to satisfy the growing demands for accurate CTE measurement of soft materials. Graphical abstract: